Orthostatic hypotension in the elderly: nursing aspects - Spirgienė, Lina; Kučikienė, Odeta (Slauga. Mokslas ir praktika, 2021)
Orthostatic hypotension is a common problem among elderly patients, associated with significant morbidity. The diagnostic evaluation requires a comprehensive history. There are a number of non-pharmacological interventions for orthostatic hypotension that are used in the elderly. With proper evaluation and nursing management, the occurrence of adverse events, including falls, fracture, functional decline, and myocardial ischemia, can be significantly reduced.